9=3/4(-12x+36)

Simple and best practice solution for 9=3/4(-12x+36) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9=3/4(-12x+36) equation:


9=3/4(-12x+36)

We simplify the equation to the form, which is simple to understand
9=3/4(-12x+36)

Reorder the terms in parentheses
9=+(-9x+27)

Remove unnecessary parentheses
+9=-9x+27

We move all terms containing x to the left and all other terms to the right.
+9x=+27-9

We simplify left and right side of the equation.
+9x=+18

We divide both sides of the equation by 09 to get x.
x=2

See similar equations:

| 6x+8y=4.1 | | 2k=7k+15 | | z+50=z+10+4z | | 3x-4(5x+7)=-130 | | 95+75x=96 | | u=(-(-2.42)±√(〖(-2.42)〗^2-4(1)(-102.64)))/(2(1)) | | y=8E-05x+0.0002 | | 99+v=5300/10 | | -20(20+-x)=100 | | -21-18=-3 | | 1/2(4x-16)=2(2x-8) | | -20(20+-x)=200 | | 5x+3y(2x)=22 | | 6m+2n+9m+8n= | | 21-18=-3 | | -20(20+-x)=800 | | x-4=40 | | 38s-10=0 | | 4y^2-6y+8y^2-5y= | | -20x+4=6+2x | | (x+2)(x-3)=2 | | 1/4x-2/3=y | | 3(k+3)=6(k-4) | | -15--4= | | -16x+5=6+5x | | 2x-1/x-7 | | 38s-4-6=0 | | 2(4-3X)=5(2-X) | | -9h++12h= | | ln(4x+2)=2.8 | | 384-400x=-56x^2-x | | 4x+9=13x |

Equations solver categories